Stability-Indicating Micelle-Enhanced Spectrofluorimetric Method For Determination of Tamsulosin Hydrochloride In Dosage Forms. - Elshahed, Mona Elsayed; Habib, Ibrahim (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
A rapid, simple and highly sensitive spectrofluorimetric method is developed for the determination of Tamsulosin hydrochloride (Tams.HCl) in pharmaceutical formulations. The proposed method is based on investigation of the fluorescence spectral behavior of Tams.HCl in a sodium dodecyl sulphate (SDS) micellar system. In aqueous solution of Tris buffer of pH 7±0.2, SDS causes marked enhancement in the fluorescence intensity of Tams.HCl (about +110%). The fluorescence intensity is measured at 328 nm after excitation at 280 nm and the fluorescence-concentration plots are rectilinear over the range 0.1-1.2 µg ml-1, with lower detection limit of 0.027 µg ml-1 and quantification limit of 0.09 µg ml-1. The method is successfully applied to the analysis of the studied drug in its commercial capsules, and the results are in good agreement with those obtained with the official method. The application of the proposed method is extended to stability studies of Tamsulosin hydrochloride after exposure to different forced degradation conditions, such as acidic, alkaline and oxidative conditions, according to ICH guidelines.